An integrated mediating and moderating model to improve service quality through job involvement, job satisfaction, and organizational commitment - Al-Refaei, Abd Al-Aziz; Mohd Ali, Hairuddin; Ateeq, Ali Ahmed; Alzoraiki, Mohammed (MDPI, 2023)
Employees’ perception of their job and organization is believed to influence service quality (SQ). Hence, this study aims to integrate a mediating and moderating model to improve SQ through job involvement (JI), job satisfaction (JS), and organizational commitment (OC), and investigate how that model incorporating JI, JS, and OC can improve SQ in higher education contexts in developing countries. This study applied a conceptual integration between employees who provide the service and customer-perceived service quality. Data collection from the respondents was performed using a two-sample research design and two sets of questionnaires. The academic staff (296 responses) and their students (1480 responses) formed the study’s sample size. Structural Equation Modelling (SEM) was used to analyze the collected data. The data analysis showed a significant impact of JS on OC and SQ (i.e., the quality of lectures they received in the classroom that shaped their learning experiences). OC significantly affected SQ and partially mediated the effect of JS and SQ. JI plays a moderator role in the JS-OC and SQ relationship. This study contributes to the literature by linking employees’ JI, JS, and OC to SQ. Employee JI, JS, and OC are crucial in promoting service quality. Practical implications for students, employees, institutions, and society were provided.